Peran Orang Tua dalam Pengembangan Kepribadian Anak pada Era Globalisasi - Victoriana, Evany (Zenit, 2012)
This paper examines theoretically the influence of parental roles to the child personality development in the globalization era. Nowdays, competitive personality with high skills, achievement motivation, good social competence, and skills to control and coping with stress are needed. To develop  children  with  those attributes, parents can develop authoritative parenting styles  with  two  dimensions:  (1)  moderate control; parents give reasonable roles and encourages mature behavior  their children; (2) high emotionality (warm and responsiveness); parents give love and care for children’s.  Keywords:  parental  roles,  child  personality  development,  globalization,  authoritative,  parenting styles.